Kritik Hadis dalam Perspektif Sejarawan - Afwadzi, Benny (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2017)
This article aims to elaborate methodological investigation of ?adîth criticism of the historians point of view. It also observes the salient differences between them and the scholars of ?adîth, as both are often on different worldview. Through descriptive-analytical study, the author comes to the conclusion that there are at least two methods of ?adîth criticism in historian perspective that are [1] critical in analysing the companions of the Prophet and [2] critical to the content (matn) of ?adîth. By shifting paradigm framework, it suggests that both of them should not be rejected. Both perspectives should be used as a method to develop the tradition of ?adîth criticism, although at some points, they have to be put on critical consideration. On the other side, the historian perspective might be useful to encourage the weaknesses which has been existed in conventional science of ?adîth criticism.